The Dnieper Cascade as part of International Waterway E40 (Geography and Tourism, 2018)
The Dnieper River has long played an important part in the development of local economy, including the transport sector. However, it was not until the construction of a cascade of hydroelectric power plants in the 20th century that it was possible to make extensive use of the river’s resources and to improve the navigation conditions. Water transport in Ukraine began to decline with the dissolution of the Soviet Union and the consequent political and economic transformations. Today, the depreciated infrastructure is one of the barriers to the development of inland water transport. However, the ongoing work to restore the Dnieper transport importance will enable Ukraine to take advantage of its geographical location that coincides with important trade routes connecting Europe with Asia. The purpose of this paper is to present the economic context of the Dnieper Cascade operation as well as its limiting and development factors by analysing literature resources, statistical data and legal documents.